Strategies With A Wask Cake Trade in The Way of Fighting Online Shop Rivalities in Sikur Village - Aini, Siska Hidayatul; Susilawati, Susilawati; Mispandi, Mispandi (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
Strategy is, in fact, planning and managing to a goal. It is also understood as a process of determining a summit leader's plan that focuses on the long-term goals of the organization, accompanied by the elaboration of a way of achieving a specific goal or to face competition. The objective of this research is to find out where wet cake traders are in the midst of online shop competition and to know what strategies the wet cookie traders in Sikur Village use in the face of online store competition. This research uses qualitative methods. The subject of the study is 10 wet pie dealers in Sikur Village. The data in this study is obtained through three methods observation, interview, and documentation. The results of this study are analyzed by reducing data, presenting data and drawing conclusions. The results of this study show that; 1) The situation of wet cake merchants in Sikur Village experienced a slight decline in buyers caused by the presence of a new trading system i.e. trading through online shops. The presence of this new trading system has strengthened the competition between traders, and it has been coupled with advances in society that have made conventional trade abandoned.  As a result, the income of most wet cake traders in Sikur Village has fallen. 2) Most wet cake dealers in Sikur Village have a special strategy to survive. The strategy used is product quality improvement strategy, price strategy, service strategy and promotion strategy.